2019
DOI: 10.1002/slct.201901873
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Adsorption and Photocatalytic Degradation of Dyes by AgI‐Bi2MoO6/Vermiculite Composite under Visible Light

Abstract: A novel efficient AgI‐Bi2MoO6/vermiculite adsorption‐photocatalyst is successfully synthesized by sol‐gel method and precipitation method. The structure and properties of AgI‐Bi2MoO6/vermiculite were analyzed by XRD, FT‐IR, XPS, SEM, TEM, BET, and DRS. All the AgI‐Bi2MoO6/vermiculite composites with different AgI content show enhanced photocatalytic performance for malachite green (MG) dye degradation compared to pure Bi2MoO6 and Bi2MoO6/vermiculite composites. The highest degradation efficiency for MG (30 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Form Figure 3, it also can be seen that the peak of MP sample is sharper than that of NS and AS, and the characteristic peaks(35.64 ο , 43.31 ο , 54.28 ο , 57.30 ο , 62.76 ο ) of Fe 3 O 4 can be seen more clearly, illustrating that the crystallinity increased by the process of crosslinking and curing. In addition, it can be obviously observed that the diffraction peaks of vermiculite, which is located at 26.80° and 29.45°, but the peak at 29.45° has a slight shift comparing with pure vermiculite (28.95°), [23] indicating that vermiculite and compound together and the two substances could cause the crystal structure distortion of vermiculite. Moreover, a series of other sharp reflections, that may be ascribed to some impurities (e. g. calcium‐containing or aluminum‐containing oxide species), were present in the samples.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Form Figure 3, it also can be seen that the peak of MP sample is sharper than that of NS and AS, and the characteristic peaks(35.64 ο , 43.31 ο , 54.28 ο , 57.30 ο , 62.76 ο ) of Fe 3 O 4 can be seen more clearly, illustrating that the crystallinity increased by the process of crosslinking and curing. In addition, it can be obviously observed that the diffraction peaks of vermiculite, which is located at 26.80° and 29.45°, but the peak at 29.45° has a slight shift comparing with pure vermiculite (28.95°), [23] indicating that vermiculite and compound together and the two substances could cause the crystal structure distortion of vermiculite. Moreover, a series of other sharp reflections, that may be ascribed to some impurities (e. g. calcium‐containing or aluminum‐containing oxide species), were present in the samples.…”
Section: Resultsmentioning
confidence: 97%
“…Given that the activated carbon/Fe 3 O 4 composite can be obtained from electric coagulation sludge, because the organic waste containing in sludge can form activated carbon by pyrolysis, and the iron species in the sludge can form magnetic Fe 3 O 4 which effectively enhance sorption effectiveness and be advantages of the separation process, [21–22] So, use electric coagulation sludge to prepare a magnetic adsorbent is a good choice for its resource utilization. In order to obtain more effective composite, vermiculite materials can bring into the composite due to its high adsorption properties, low‐cost, non‐hazardous and easily available [23–24] …”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of exploring the possible mechanism of photodegradation for the AGU−1% composite photocatalyst under visible light, ethylenediamine benzoquinone (BQ), isopropanol (IPA), and tetraacetic acid disodium salt (EDTA−2Na) were added as the scavengers for superoxide radicals (•O 2 − ), hydroxyl radicals (•OH), and holes (h + ) during the degradation (Figure 8a). 56 In the LVF degradation system for the AGU−1% composite photocatalyst, the degree of contribution (oxidation) of different active species is in the order of •OH < •O 2 − < h + . Therefore, •O 2 − and h + act as the major active substances and •OH is not the substance playing a major role in oxidation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They found that KNbO 3 nanoneedles were grown on the outer and inner surface of layered vermiculite and abundant active sites in the 3D framework are favorable for photocatalytic activity. Additionally, Zhu et al could fabricate an efficient ternary AgI-Bi 2 MoO 6 /vermiculite adsorption-photocatalyst with superior photoactivity under visible light [39]. This composite showed high photodegradation efficiency of malachite green of about 98.89%, which was much better than that of Bi 2 MoO 6 (54.89%) and Bi 2 MoO 6 /vermiculite (80.74%).…”
Section: Vermiculite-supported Photocatalystmentioning
confidence: 99%